Lived religion: faith and practice in everyday life - McGuire, Meredith B. (Oxford University Press, 2008)
The divergence of religious practices from one individual to another has long baffled scholars of religion. In this book Meredith McGuire points the way forward toward a way of understanding and studying religious behaviour by exploring the many ways that people express themselves spiritually